(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Motivation is the method of influencing individuals to attain specified goal. It is a desire to fulfill an action. It includes desire, interest, beliefs, intentions or necessities. The remittance is the money sent in Payment. Remittance refers to money that is sent or transferred to another party. It is the process of making payment from an account. It is an act of payment of money by submitting a written request. In other words, it is a process of transfer of money through Electronic Fund Transfer and Automated Disbursement. Prime Minister Jeevan Jyothi Bima Yojana is a government – backed life insurance scheme of India. It is a pure term insurance policy which covers only mortality with no investment component and has a life cover of Rs.2 lakh. It is an auto-renewable system. The cover period is 1st June of each year to 31st May of subsequent years. Nearly 28 crore people joined under this scheme and the total number of claims settled till May 2022 were nearly 4,69,548 in India. This scheme is available to people in the age group of 18 to 50 years.